(untitled) (المجلة الدولية للبحوث العلمية, 2026)
The aims of this study were to develop a spinal lesion scale for the research sample, to assess the level of spinal cord damage among the research participants, and to find out what a wallet in your back pocket has to do with spinal injuries. The researcher hypothesized that there is a statistically significant relationship between carrying a wallet in the back pocket and spinal injuries. The study sample was limited to 200 people. The sample was limited to males aged 20–40 years and may not be representative of other age groups and females. The researcher extracted the following data from the individuals using the statistical bag (SPSS), arithmetic mean, independent samples (t) test, and percentage. The researcher applied the proper statistical procedures and discovered a statistically significant correlation between holding a wallet in a back pocket and spinal injury. The researcher suggested the wallet should be kept in the front pocket or in a separate bag/handbag. Also, practice stretching the piriformis muscle and pelvic muscles to equalize the sometimes-pressure that the body was subjected to.